Edukasi Penerapan Perilaku Hidup Bersih Dan Sehat Di Rw 08 Desa Sirnagalih - Nurjanah, Imas; Amalia , Dila; Febriana, Dwi; Fitriyanti, Lisa; Rahmawati; Eliyuda Yusup, Silvi (Pusat Riset dan Inovasi Nasional, 2024)
PHBS is all health behavior carried out with awarness so that family members help themselves in the field of health and play an active role in health activities in the community. But currently there are still many. who are attacked by disease, as a result of not implementing clean and healthy living habits in the household. The aim of the research is to determine the level of knowledge of the community regarding Clean and Healthy Living Behavior. This research is an analytical observational study with a cross-sectional design and was carried out by 5 students at RW08, Sirnagalih Village, Taman Sari District, bogor regency in 2024. The method was carried out in this community service is by means of counseling because in our opinion this method is very effective in being used as a tool for the community regarding clean and healthy living behavior. The researchers observed that the community already has good knowledge regarding clean and healthy living behavior, but before providing